Locally advanced duodenal gangliocytic paraganglioma treated with adjuvant radiation therapy: case report and review of the literature - Wong, Adrian (BioMed Central, 2005)
BACKGROUND: Gangliocytic paraganglioma are rare neoplasms that predominantly arise in periampulary region. Though considered benign the disease can spread to regional lymphatics. CASE PRESENTATION: A 49 year old woman presented with melena and was found to have a periampullary mass. Endoscopic evaluation and biopsy demonstrated a periampullary paraganglioma. The tumor was resected with pylorus-preserving pancreaticoduodenectomy and was found to represent a gangliocytic paraganglioma associated with nodal metastases. In a controversial decision, the patient was treated with adjuvant external beam radiation therapy. She is alive and well one year following resection. The authors have reviewed the current literature pertaining to this entity and have discussed the biologic behavior of the tumor as well as the rationale for treatment strategies employed. CONCLUSION: Paraganglioma is a rare tumor that typically resides in the gastrointestinal tract and demonstrates low malignant potential. Due to rarity of the disease there is no consensus on the adjuvant treatment even though nearly 5% of the lesions demonstrate the malignant potential.